Ácidos orgânicos e microbiota cecal anaeróbia no controle da infecção experimental de frangos por Salmonella typhimurium e Salmonella enteritidis - Andreatti, R. L.; da Silva, E. N.; Curi, P. R. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1997)
The aim of this investigation was to study the effect of organic acids and/or anaerobic cecal microflora (ACM) on systemic and digestive infection of broilers by Salmonella typhimurium and S. enteritidis. ACM was used without previous bacterial identification. The treatment with ACM increased the resistance to Salmonella spp infection. Infection was more evident in caeca, followed by rectum and crop and did not interfere on body weight of broilers. Treated and control groups showed the same degree of infection at the end of the experiment. The use of ACM isolated or combined with acetic acid, reduced the colonization of the chick's digestive system by S. typhimurium and S. enteritidis. Acetic acid added to ACM did not potentiate the reduction of digestive system colonization. Except for the crop, the isolated use of acetic, propionic or formic acids did not reduce S. typhimurium and S. enteritidis, in caeca and rectum. The use of organic acids and ACM had little effect on reduction of caecum pH. The treatment with ACM reduced the quantity of S. enteritidis in the faeces. The reduction of caecum pH did not reduce the quantity of S. enteritidis in faeces. S. enteritidis was much more invasive than S. typhimurium and use of organic acids and ACM had little effect on reduction of systemic infection.
Organic acids an anaerobic microflora for control of experimental infection of broilers by Salmonella typhimurium and S-enteritidis
Keywords: Salmonella typhimurium; Salmonella enteritidis; anaerobic cecal microflora; broiler